2018
DOI: 10.32327/ijmess/7.4.2018.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fit between Manufacturing Strategy, Strategic Orientation, and Marketing Strategy on Business Performance

Abstract: Marketing usually acts as the channel of communication between the marketing environment, and customer preference and usually deals with revenue maximization, whereas manufacturing usually is responsible for receiving the design for production and cost minimization (Brooksbank, 1991;Lilien and Weinstein, 1984).However, marketing and manufacturing are organizationally separated in most firms (Karmarkar and Lele, 2005;Jüttner, Christopher and Godsell, 2010). Therefore, the strategic alignment between marketing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Serviceoriented manufacturing firms prioritize market-related considerations during their early stages to gain a competitive edge in their industry, leading to significant improvements in overall enterprise performance. At this stage, firms focus on softer service-level elements, such as product customization and enhancing customer experience, rather than on the more tangible, functional-level factors like technical specifications or product quality (Feng et al, 2021;Chen, 2010). However, expanding other types of services can result in costs associated with them exceeding the expected revenue growth, which may not lead to increased performance.…”
Section: The Impact Of Servitization Intensity On Firm Productivitymentioning
confidence: 99%
“…Serviceoriented manufacturing firms prioritize market-related considerations during their early stages to gain a competitive edge in their industry, leading to significant improvements in overall enterprise performance. At this stage, firms focus on softer service-level elements, such as product customization and enhancing customer experience, rather than on the more tangible, functional-level factors like technical specifications or product quality (Feng et al, 2021;Chen, 2010). However, expanding other types of services can result in costs associated with them exceeding the expected revenue growth, which may not lead to increased performance.…”
Section: The Impact Of Servitization Intensity On Firm Productivitymentioning
confidence: 99%
“…(3) Inverted U-type relationship. Chen (2010) compared the manufacturing enterprises in China and America and found that the servitization of Chinese manufacturing enterprises has a significant inverted U-type relationship with their economic benefits, while the American manufacturing enterprises have a single positive relationship. (4) Saddle-type relationship.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…On the one hand, it may lead to conflicts between product-related resources and service-oriented resources. On the other hand, the unclear boundary of service scope can result in the mismatch between resources and business services (Chen, 2010), thus ultimately giving rise to resource allocation, not in line with the firm strategies, then inevitably leading to the decline of business performance. (4) Changing service demands of customers.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%